Nanomaterials and Nanotechnology-Associated Innovations against Viral Infections with a Focus on Coronaviruses - Nasrollahzadeh, Mahmoud; Sajjadi, Mohaddeseh; Soufi, Ghazaleh Jamalipour; Iravani, Siavash; Varma, Rajender S (Nanomaterials (Basel, Switzerland), 2020)
Viral infections have recently emerged not only as a health threat to people but rapidly became the cause of universal fatality on a large scale. Nanomaterials comprising functionalized nanoparticles (NPs) and quantum dots and nanotechnology-associated innovative detection methods, vaccine design, and nanodrug production have shown immense promise for interfacing with pathogenic viruses and restricting their entrance into cells. These viruses have been scrutinized using rapid diagnostic detection and therapeutic interventional options against the caused infections including vaccine development for prevention and control. Coronaviruses, namely SARS-CoV, MERS-CoV, and SARS-CoV-2, have endangered human life, and the COVID-19 (caused by SARS-CoV-2) outbreak has become a perilous challenge to public health globally with huge accompanying morbidity rates. Thus, it is imperative to expedite the drug and vaccine development efforts that would help mitigate this pandemic. In this regard, smart and innovative nano-based technologies and approaches encompassing applications of green nanomedicine, bio-inspired methods, multifunctional bioengineered nanomaterials, and biomimetic drug delivery systems/carriers can help resolve the critical issues regarding detection, prevention, and treatment of viral infections. This perspective review expounds recent nanoscience advancements for the detection and treatment of viral infections with focus on coronaviruses and encompasses nano-based formulations and delivery platforms, nanovaccines, and promising methods for clinical diagnosis, especially regarding SARS-CoV-2.
Keywords: viral infections; coronaviruses; quantum dots; graphene oxide; nanovaccines; nanoparticles; SARS-CoV-2; COVID-19; nanotechnology